Cardiopulmonary fitness in children with asthma versus healthy children. Issue 3 (29th November 2022) - Moreau, Johan; Socchi, Floriane; Renoux, Marie Catherine; Requirand, Anne; Abassi, Hamouda; Guillaumont, Sophie; Matecki, Stefan; Huguet, Helena; Avesani, Martina; Picot, Marie-Christine; Amedro, Pascal
Abstract : Objectives: To evaluate, with a cardiopulmonary exercise test (CPET), the cardiopulmonary fitness of children with asthma, in comparison to healthy controls, and to identify the clinical and CPET parameters associated with the maximum oxygen uptake (VO2max ) in childhood asthma. Design: This cross-sectional controlled study was carried out in CPET laboratories from two tertiary care paediatric centres. The predictors of VO2max were determined using a multivariable analysis. Results: A total of 446 children (144 in the asthma group and 302 healthy subjects) underwent a complete CPET. Mean VO2max was significantly lower in children with asthma than in controls (38.6±8.6 vs 43.5±7.5 mL/kg/min; absolute difference (abs. diff.) of −4.9 mL/kg/min; 95% CI of (−6.5 to −3.3) mL/kg/min; p<0.01) and represented 94%±9% and 107%±17% of predicted values, respectively (abs. diff. −13%; 95% CI (−17 to −9)%; p<0.01). The proportion of children with an impaired VO2max was four times higher in the asthma group (24% vs 6%, p<0.01). Impaired ventilatory efficiency with increased VE/VCO2 slope and low breathing reserve (BR) were more marked in the asthma group. The proportion of children with a decreased ventilatory anaerobic threshold (VAT), indicative of physical deconditioning, was three times higher in the asthma group (31% vs 11%, p<0.01). Impaired VO2max was associated with female gender, high body mass index (BMI), FEV1, low VAT and high BR. Conclusion: Cardiopulmonary fitness in children with asthma was moderately but significantly altered compared with healthy children. A decreased VO2max was associated with female gender, high BMI and the pulmonary function. Trial registration number: NCT04650464 .